Pengaruh Fitur, Variasi Produk, dan Kemudahan Transaksi terhadap Kepuasan Pengguna Mobile Banking pada Lembaga Keuangan Perbankan Syariah di Kota Jambi - M. Farhan; Eja Armaz Hardi; Syahril Ahmad (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
This research aims to determine the influence of features, product variations and ease of transactions on mobile banking user satisfaction at sharia banking financial institutions in Jambi City. This research used a quantitative approach which was carried out by distributing questionnaires to 112 Mobile Banking users in Jambi City. The methods used in this research are instrument tests (validity and reliability tests), classical assumption tests (normality, multicollinearity and heteroscedasticity tests) and multiple liner analysis along with statistical tests (t test, F test and R2 Determination Coefficient). The results of this research show that features have a positive and significant effect on user satisfaction which can be determined using the t test with a significance value of 0.001 < 0.05 and a value of tcount > ttable, namely 3.426 > 0.198217. Product variations have a positive and significant effect on user satisfaction as evidenced by the significance value of 0.001 < 0.05 and the tcount > ttable value, namely 3.577 > 0.198217. ease of transactions has a positive and significant effect on user satisfaction which can be seen with a significance value of 0.001 < 0.05 and a value of tcount > ttable, namely 3.385 > 0.198217. Simultaneously, features, product variations and ease of transactions have a positive and significant effect on mobile banking user satisfaction at sharia banking financial institutions which can be seen from the F test, namely fcount > ftable or 40.058 > 2.69 and the resulting significance value is 0.000 < 0.005. The determinant coefficient value is 0.514 or 51.4% and the remaining 0.486 or 48.6% can be explained by other variables outside this research.